An analysis of questions and responses in gotcha calls / Yasotha A/P Kanesan - Yasotha, Kanesan (2013)
This study uses conversation analysis to investigate questions and question-response sequences in a semi-casual conversation like prank calls. The conversation in the Gotcha prank calls are built upon question-response sequences. The study aims to find out what types of questions are constructed in Gotcha calls and to what extent would the negotiation of questions and responses show power in Gotcha calls. Thirty Gotcha prank calls related to financial issues were selected for the analysis. The analysis of the question-response sequences was done based on an adapted coding scheme by Stivers & Enfield (2010) and Wang (2006). The questions were categorised based on the functions of the questions in the conversation. Thus, the questions were grouped based on the social action of the question which was either to request for information, request for confirmation, to suggest, make assessment or initiation of repair. The findings show that request for information was primarily used to get facts related to the fabricated situations. Questions were also divided into Yes/No questions and Wh-questions while the responses were divided into answers, non answers or no response. The Yes/No questions restrict the responses and show authority while the answers prove to have the authoritative questions accomplishes its demands. The pranksters dominated majority of the calls using their institutional power while the victims of the calls also dominated some calls using their strong knowledge schema to demonstrate authority over the pranksters. The study also adds on to studies on prank calls which are hugely lacking in the field of pragmatics.